2011
DOI: 10.1371/journal.pone.0027390
|View full text |Cite
|
Sign up to set email alerts
|

Are Helicobacter Pylori and Other Helicobacter Species Infection Associated with Human Biliary Lithiasis? A Meta-Analysis

Abstract: BackgroundSince the isolation of Helicobacter species in biliary system, a hypothetical question was raised about the role of these agents in the development of cholelithiasis. This meta-analysis is to explore the association between the Helicobacter infection and biliary lithiasis.Methodology/Principal FindingsA systematic literature search was performed to identify all eligible articles. Meta-analysis which was carried out using odds ratio and random effect model, 95% confidence intervals for odds ratio was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 51 publications
(103 reference statements)
2
36
0
3
Order By: Relevance
“…Our previous meta-analysis demonstrated that Helicobacter pylori ( H.pylori ) in human biliary system was correlated with chronic cholecystitis, especially in the regions with higher prevalence of this infectious agent such as South Asia, East Asia and Latin America. [6] Evidences supporting the association between H.pylori infection and chronic cholecystitis could be found by using direct culture or staining of H.pylori in gallbladder tissues as well as indirect techniques such as PCR, ELISA and serology for detecting H.pylori -specific genes or antibodies [7][9]. The positive rate of H.pylori in gallbladder is reported to be 10%–20% by culture.…”
Section: Introductionmentioning
confidence: 99%
“…Our previous meta-analysis demonstrated that Helicobacter pylori ( H.pylori ) in human biliary system was correlated with chronic cholecystitis, especially in the regions with higher prevalence of this infectious agent such as South Asia, East Asia and Latin America. [6] Evidences supporting the association between H.pylori infection and chronic cholecystitis could be found by using direct culture or staining of H.pylori in gallbladder tissues as well as indirect techniques such as PCR, ELISA and serology for detecting H.pylori -specific genes or antibodies [7][9]. The positive rate of H.pylori in gallbladder is reported to be 10%–20% by culture.…”
Section: Introductionmentioning
confidence: 99%
“…have been identified and several of them are associated with various chronic digestive diseases (Zhou et al, 2011). H. pullorum has been related to diarrhea, gastroenteritis and liver disease in humans (Ceelen et al, 2005).…”
Section: Resultsmentioning
confidence: 99%
“…However, its definite role and relation in the gallbladder diseases have not been well defined. In the meta-analysis published by Zhou et al 26 in 2011, showed that the Helicobacter detection rate in gallbladder to range from 3.02% to 80%. The detection rate varied with the type of methods used.…”
Section: Discussionmentioning
confidence: 99%